Role of MHC-Linked Susceptibility Genes in the Pathogenesis of Human and Murine Lupus - Manfred Relle; Andreas Schwarting (Clinical and Developmental Immunology)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by the production of autoantibodies against nuclear antigens and a systemic inflammation that can damage a broad spectrum of organs. SLE patients suffer from a wide variety of symptoms, which can affect virtually almost any tissue. As lupus is difficult to diagnose, the worldwide prevalence of SLE can only be roughly estimated to range from 10 and 200 cases per 100,000 individuals with dramatic differences depending on gender, ethnicity, and location. Although the treatment of this disease has been significantly ameliorated by new therapies, improved conventional drug therapy options, and a trained expert eye, the underlying pathogenesis of lupus still remain widely unknown. The complex etiology reflects the complex genetic background of the disease, which is also not well understood yet. However, in the past few years advances in lupus genetics have been made, notably with the publication of genome-wide association studies (GWAS) in humans and the identification of susceptibility genes and loci in mice. This paper reviews the role of MHC-linked susceptibility genes in the pathogenesis of systemic lupus erythematosus.